Navigation of vertebro-pelvic fixations based on CT-fluoro matching - Marintschev, Ivan (Springer-Verlag, 2010)
Different navigation procedures (based on 2D-, 3D-fluoroscopy or CT modalities) with their respective limitations are established in orthopedic surgery. The hypothesis is that intraoperative matching of different modalities (fluoro and CT) increases the precision of navigated screw placement and reduces the fluoroscopy time. Vertical unstable pelvic ring fractures of 12 patients were treated with vertebro-pelvic fixations (6 in the standard technique and 6 using the fluoro-CT navigation). An optimal osseous corridor could be determined by the navigation procedure increasing the overall precision of screw placement (no misplacement in the second group as compared to one malplaced pedicle screw in the standard group). The achieved screw lengths were [(mean ± SE) 78 ± 5 vs. 53 ± 4 mm, p < 0.001). Less invasive open approaches and a reduction of fluoroscopy time (time per screw in seconds: 121 vs. 62 s) were observed. CT-fluoro-matched navigation improves the intraoperative visualization of osseous structures and increases the precision of screw placement with less radiation exposure.